Prospective Evaluation of Virtual MR Elastography With Diffusion‐Weighted Imaging in Subjects With Nonalcoholic Fatty Liver Disease - Hanniman, Elyisha; Costa, Andreu F.; Bowen, Chris V.; Abdolell, Mohamed; Stueck, Ashley; McLeod, Magnus; Peltekian, Kevork; Rioux, James; Clarke, Sharon E. (Journal of magnetic resonance imaging, 2022)
Background Non‐alcoholic fatty liver disease (NAFLD) is increasingly common worldwide and can lead to the development of cirrhosis, liver failure and cancer. Virtual magnetic resonance elastography (VMRE), which is based on a shifted apparent diffusion coefficient (sADC), is a potential noninvasive method to assess liver fibrosis without the specialized hardware and expertise required to implement traditional MR elastography (MRE). Although hepatic steatosis is known to confound ADC measurements, previous studies using VMRE have not corrected for hepatic fat fraction. Purpose To compare VMRE, corrected for the confounding effects of unsuppressed fat signal, to MRE and biopsy in subjects with suspected NAFLD. Study Type Prospective, cross‐sectional. Population A total of 49 adult subjects with suspected NAFLD (18 male; median age 55 years, range 33–74 years) who underwent liver biopsy. Field strength/Sequence 3T, diffusion‐weighted spin echo planar, chemical‐shift encoded (IDEAL IQ) and MRE sequences. Assessment Two observers drew regions of interest on sADC, proton density fat fraction and MRE‐derived stiffness maps. Fat‐corrected sADC values were used to calculate the diffusion‐based shear modulus according to the VMRE method. Predicted fibrosis stage for MRE and VMRE was determined using previously published cut‐off values. Statistical Tests The relationship between VMRE and MRE was assessed with least‐squares linear regression (coefficient of determination, R2). Agreement between MRE and VMRE‐predicted fibrosis stage was evaluated with a kappa coefficient and accuracy compared using McNemar's test. A one‐way ANOVA determined if the fat‐corrected sADC (VMRE) and MRE differed by fibrosis stage. A P value < 0.05 was considered statistically significant. Results Least squares regression of VMRE vs. MRE revealed R2 = 0.046 and a slope that was not significantly different from zero (P = 0.14). There was no agreement between MRE and VMRE‐predicted fibrosis stage (kappa = −0.01). The proportion of correctly predicted fibrosis stage was significantly higher for MRE compared to VMRE. MRE was significantly associated with fibrosis stage, but fat‐corrected sADC was not (P = 0.24). Data Conclusion Fat‐corrected VMRE was not associated with fibrosis stage in NAFLD. Further investigation is required if VMRE is to be considered in subjects with NAFLD. Evidence Level 1 Technical Efficacy Stage 2